2022
DOI: 10.3389/fimmu.2022.955063
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune checkpoint inhibitor resistance is associated with melanoma sub-types exhibiting invasive and de-differentiated gene expression signatures

Abstract: Melanoma is a highly aggressive skin cancer, which, although highly immunogenic, frequently escapes the body’s immune defences. Immune checkpoint inhibitors (ICI), such as anti-PD1, anti-PDL1, and anti-CTLA4 antibodies lead to reactivation of immune pathways, promoting rejection of melanoma. However, the benefits of ICI therapy remain limited to a relatively small proportion of patients who do not exhibit ICI resistance. Moreover, the precise mechanisms underlying innate and acquired ICI resistance remain uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…These cells also have reduced IFNγ signaling activity (Fig 5D). This trajectory was recently reported in experimental data demonstrating that melanoma patients responding to anti-PD-1 therapy exhibit a more proliferative gene expression signature, while the non-responders were enriched in invasive and neural crest-like phenotypes (59). Moreover, vemurafenib-resistant clones of A375 and 451Lu cells display similar molecular attributes (Fig 5E).…”
Section: Combinatorial Control Of Pd-l1 Levels By Ifnγ Signaling and ...supporting
confidence: 80%
“…These cells also have reduced IFNγ signaling activity (Fig 5D). This trajectory was recently reported in experimental data demonstrating that melanoma patients responding to anti-PD-1 therapy exhibit a more proliferative gene expression signature, while the non-responders were enriched in invasive and neural crest-like phenotypes (59). Moreover, vemurafenib-resistant clones of A375 and 451Lu cells display similar molecular attributes (Fig 5E).…”
Section: Combinatorial Control Of Pd-l1 Levels By Ifnγ Signaling and ...supporting
confidence: 80%
“…Although immune checkpoint inhibitor-based therapies are somewhat more promising than targeted therapies in achieving complete cures, for most patients, intrinsic or acquired resistance remains a key obstacle. Hossain et al (2022) [ 50 ] showed that non-responding melanomas to anti-PD1 therapy are enriched for genes characteristic of undifferentiated and neural crest-like differentiation states, while in contrast, responding melanomas to anti-PD1 therapy exhibit expression signatures mainly characterized by transitory and melanocytic state gene signatures, supporting the notion that phenotype switching behavior characterizes responding versus non-responding melanomas ( Figure 1 ). The same study also showed an association between phenotype switching, immune cell composition in the TME, and the presence of innate resistance to anti-PD1 therapy.…”
Section: The Rheostat Model Of Mitfmentioning
confidence: 70%
“…To this end, ICI therapies have revolutionized the treatment of melanoma, but innate and acquired resistance remain as clinical challenges. Furthermore, clinical studies have shown that ICI resistance is associated with changes in TME composition (61, 62).…”
Section: Resultsmentioning
confidence: 99%